A Comparative Efficiency Study of Two Adsorbent Materials to Remove Eosin Y Dye from Aqueous Solutions - Baghdad Science Journal (مجلة بغداد للعلوم, 2018)
This study was done to find a cheap, available and ecofriendly materials that can remove eosin y dye from aqueous solutions by adsorption in this study, two adsorbent materials were used, the shells of fresh water clam (Cabicula fluminea) and walnut shells. To make a comparison between the two adsorbents, five experiments were conducted. First, the effects of the contact time, here the nut shell removed the dye quickly, while the C. flumina need more contact time to remove the dye. Second, the effects of adsorbent weight were examined. The nut shell was very promising and for all used adsorbent weight, the R% ranged from 94.87 to 99.29. However C. fluminea was less effective in removing the dye with R% ranged from 47.59 to 55.39. The third experiment was initial dye concentration. The C. fluminea showed very low ability to remove eosin y , while the nut shell was more effective in removing the dye with R% up to 97.36 and an inverse correlation between the increase of initial dye concentration and R%. The fourth experiment was the effect of pH value of the solution and the adsorbent particles size. The results show that fine particles were more effective than granular particles. Throughout the whole study, the walnut shell was very promising in removing the dye, while the C. fluminea shell was much less effective than the walnut shell.